Spinal Tumor Surgery- Our Experiences of 35 Cases in a Peripheral Hospital in Bangladesh (Medicine Today, 2021)
Introduction: Surgical outcome of spinal tumour varies depending on a number of factors such as: site of the tumour, compression within the spinal canal, the histological characteristics of the tumour, the neurological progression and initial response to corticosteroid therapy, patient’s age, comorbidity, tumour extension, involvement of neighboring structures and organs etc.Materials & Methods: The 35 patients with spinal tumour underwent surgery by our team in 10 years (January 2009 - December 2018) were reviewed retrospectively.Results: Analysis of the surgical outcome of our spinal tumour patients was done on different variables like age, sex, presenting symptoms, neuroimaging, comorbidities etc. The aim of surgery was decompression of the spinal cord, total removal of the tumour when possible and spinal stabilization when needed. Out of our 35 patients with spinal tumour, extradural tumour comprises 8, intradural extramedullary tumour 25 and intramedullary tumour 2.Conclusion: The aim of this study is to analyze the data to made conclusion for more effective strategy as per site, size, type, resectibility and histological variety to establish and effective treatment protocol and prevention of per-operative and post-operative complications. Intradural extramedullary tumour can be radically resected with no mortality and minimal peri-operative morbidity. But resection of intramedullary spinal tumour is difficult, hazardous and usually incomplete, so needs much more skilled and meticulous surgical hands.Medicine Today 2021 Vol.33(1): 38-41